INTEGRATING SERVQUAL AND SPIRITUAL VALUES IN IMPROVING TEMPLE CONGREGATION SATISFACTION: A QUANTITATIVE STUDY ON URBAN BUDDHIST COMMUNITIES IN INDONESIA (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
The quality of service and spiritual values play an important role in shaping the satisfaction of the congregation, especially in the Vihara environment which functions not only as a place of worship, but also as a center for moral and spiritual formation. This study aims to empirically examine the influence of service quality (SERVQUAL) and spiritual values on the satisfaction of the congregation at Panna Sikkha Temple, Jakarta. Using a quantitative approach, data were collected from 168 respondents through an online questionnaire and analyzed using multiple linear regression. The research instrument showed very high reliability (α = 0.933), indicating strong internal consistency. The regression results showed that the quality of service and spiritual values simultaneously had a significant effect on the satisfaction of the congregation, with an R² value of 0.713. Key findings confirm that the dimensions of SERVQUAL—especially empathy, assurance, and responsiveness—as well as spiritual values such as understanding the Dharma and the meaning of life, are strong predictors of congregation satisfaction. The context of the monastery as a socio-religious institution makes the integration of technical and spiritual aspects a strategic need in improving the experience of the congregation.